Stakeholder Perceptions of the Implementation of the Independent Campus Independent Learning Policy - Jaenuddin, Mohammad; Natsir, Nanat Fatah (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
This study aims to determine the response of Stakeholders to the Implementation of MBKM at UIN Sunan Gunung Djati Bandung (Research on Community Users of Graduates in Garut Regency, Bogor Regency and Cianjur Regency). This research uses a qualitative approach, the method used in this research is descriptive analytic research method Data collection techniques to be carried out in this study are observation, interviews, and documentary studies. The results of his research show that the purpose of implementing the values of the four pillars of nationality is very important in building student character so that there are no deviations in understanding about nationality and statehood, and are not easily influenced by bad things. The implementation of the four pillars of nationality in shaping the character of UIN Sunan students Gunung Djati Bandung cannot be separated from its supporting and inhibiting factors. Among the supporting factors in the implementation of the four pillars of nationality include lecturers being given 'freedom' in creativity, including in carrying out learning designs and in developing material for the four pillars of nationality. Penelitian ini bertujuan untuk mengetahui respon Stakeholder terhadap Implementasi MBKM di UIN Sunan Gunung Djati Bandung (Penelitian pada Masyarakat Pengguna Lulusan di Kabupaten Garut, Kabupaten Bogor dan Kabupaten Cianjur).Penelitian ini menggunakan pendekatan kualitatif, Metode yang digunakan dalam penelitian ini adalah metode penelitian deskriptif analitik Teknik pengumpulan data yang akan dilakukan dalam penelitian ini adalah observasi, wawancara, dan studi dokumentatif. Hasil penelitiannya menunjukkan bahwa tujuan implementasi nilai-nilai empat pilar kebangsaan merupakan hal yang sangat penting dalam membangun karakter mahasiswa agar tidak terjadi penyimpangan pemahaman tentang kebangsaan dan kenegaraan, serta tidak mudah terpengaruh oleh hal-hal buruk Pelaksanaan empat pilar kebangsaan dalam membentuk karakter mahasiswa UIN Sunan Gunung Djati Bandung tidak telepas dari faktor-faktor pendukung dan penghambatnya. Di antara faktor pendukung dalam pelaksanaan empat pilar kebangsaan di antaranya Dosen diberi ‘kebebasan’ dalam berkreativitas, termasuk dalam melakukan desain pembelajaran dan dalam mengembangkan materi empat Pilar kebangsaan.